APLIKASI BIOINFORMATIKA PADA STUDI GENETIK JAGUNG PROVITAMIN A - Aqil, Muhammad; Pabendon, M. B.; Andayani, Nining Nurini (Informatika Pertanian, 2017)
One type of functional maize that is currently studied and developed at Indonesian Cereals Research Institute is rich beta carotene maize (Pro vitamin A maize). This study aims to study the bioinformatics aspect of beta carotene maize as a basis in the determination of appropriate crossing combinations in generating pro vitamin A maize. Genetic studies used 15 high vitamin A maize inbreeds originating from within and outside the country (Cimmyt Mexico introduction). The study was conducted from April to July 2015 at the Molecular Biology Laboratory of Indonesian Cereals Research Institute. Preparation and DNA scoring were performed by using NTSYS-pc 2.1 version for generating dendogram/ data clustering. The results showed that the genetic diversity analysis based on UPGMA against genetic similarity matrix in the form of a dendogram of genetic similarity coefficient values obtained ranged from 0.36 to 0.91. The result of genetic diversity clustering of 15 inbreeds of Pro vitamin A maize in genetic similarity of 0.44 is divided into four groups: groups I, II, III and IV. Dendrogram shows groups I and II at the GD level of 0.44. Group III is at the level of GD 0.45 and divided into two sub groups namely A1 and A2. Group IV is at GD 0.503 level divided into four sub groups namely B1, B2, B3 and B4. The genetic clustering of inbreds tested indicated that the variability of the material characterized was relatively high and enables inbreds recombination in developing new varieties.